Contact killing of bacterial pathogens on metallic copper : a thesis presented in partial fulfillment of the requirements for the degree of Master of Science in Microbiology at Massey University, Auckland, New Zealand - Liu, Sha (Massey University, 2016)
Hospital-acquired infections (HAIs) are a serious health concern worldwide. Currently in New Zealand, about one in ten patients admitted to hospitals will acquire an infection while receiving treatments for other medical or surgical conditions. An emerging strategy for HAIs prevention is to use self-sanitising copper surfaces on items commonly touched in hospitals, which can provide sustained protection against microbial contamination. This is due to the fact that a wide range of microorganisms can be rapidly killed on copper in a process termed “contact killing”. However, the mechanisms of copper-mediated contact killing are not fully understood; and moreover, the potential of bacterial pathogens to develop resistance to metallic copper has so far not been examined. Here we hypothesize that bacteria are predominantly killed by a burst release of toxic copper ions resulted from chemical reactions between surface components of bacterial cell and metallic copper. To test this copper ion burst release hypothesis, we isolated and phenotypically characterized small colony variants (SCVs) derived from the two most common nosocomial pathogens, Staphylococcus aureus and Pseudomonas aeruginosa. Consistent to our expectation, SCV mutants overproducing exopolysaccharides (EPS) are more rapidly killed than wild type on the surfaces of pure copper (99.9% Cu) and brass (63.5% Cu). Similar results were obtained with a panel of mutants with altered production of cell surface components (EPS, lipopolysaccharides, capsules, flagella and pili) in a non-pathogenic model organism of Pseudomonas fluorescens SBW25. Next, a unique approach of experimental evolution was used to assess the potential emergence of bacterial resistance to metallic copper. Specifically, P. fluorescens SBW25 was subjected to daily passage of sub-lethal conditions on the surfaces of brass. After 100 daily transfers, the evolved strains had a slight increase of survival rate on brass; but importantly, ~97% of cells can still be killed on brass within one hour. Taken together, our results clearly indicate that the rate of bacterial killing on copper is largely determined by surface components of a bacterial cell, providing support for the copper ion burst release hypothesis. Our primary data of experimental evolution showed that bacteria have limited ability to evolve resistance to metallic copper.
Keywords: Pathogenic bacteria; Physiology; Evolution; Copper toxicology; Copper ions; Nosocomial infections; Prevention